2010
DOI: 10.1111/j.1364-3703.2010.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

The roles of plant phenolics in defence and communication during Agrobacterium and Rhizobium infection

Abstract: Phenolics are aromatic benzene ring compounds with one or more hydroxyl groups produced by plants mainly for protection against stress. The functions of phenolic compounds in plant physiology and interactions with biotic and abiotic environments are difficult to overestimate. Phenolics play important roles in plant development, particularly in lignin and pigment biosynthesis. They also provide structural integrity and scaffolding support to plants. Importantly, phenolic phytoalexins, secreted by wounded or oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
252
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 425 publications
(261 citation statements)
references
References 160 publications
(167 reference statements)
4
252
0
5
Order By: Relevance
“…Coumestans are phenolic compounds (aromatic benzene ring compounds with one or more hydroxyl groups) that are produced by plants (Figure 1), mainly for protection against stress. Coumestans are not phenolic alexins, similar compounds which are secreted by perturbed plants and have anti-microbial properties [81]. Coumestan infertility has not attracted as much attention as isoflavone fertility which has been greatly reduced by genetic improvement and by the decommercialisation of 'highly oestrogenic' cultivars of Trifolium species.…”
Section: Coumestansmentioning
confidence: 99%
“…Coumestans are phenolic compounds (aromatic benzene ring compounds with one or more hydroxyl groups) that are produced by plants (Figure 1), mainly for protection against stress. Coumestans are not phenolic alexins, similar compounds which are secreted by perturbed plants and have anti-microbial properties [81]. Coumestan infertility has not attracted as much attention as isoflavone fertility which has been greatly reduced by genetic improvement and by the decommercialisation of 'highly oestrogenic' cultivars of Trifolium species.…”
Section: Coumestansmentioning
confidence: 99%
“…In accordance with these suggestions, the literature survey found that the marine red algae are rich sources of phenolic compounds especially bromophenols. The biological properties of polyphenols include antioxidant (Bhattacharya et al, 2010) and anticancer (Borchardt et al, 2008) effects. Furthermore, tannis and flavonoids are defined as naturally occurring seaweed polyphenolic compounds which have been found only in marine algae (Li et al, 2010).…”
Section: 4311 Cytotoxicity Of Biosynthesized Gold Nanoparticles Withmentioning
confidence: 99%
“…Anthraquinones, flavonoids, tannins and phenolic compounds are some of the compounds constituting the phenolics. Plants produced this group of compounds mainly to fight against stress (Bhattacharya et al, 2010). This study revealed the presence of flavonoids and tannins and phenolic compounds in the I. pes caprae (Linn.)…”
Section: Resultsmentioning
confidence: 99%